Realitinship of Peer Social Interaction with Student Learning Motivation - Nanda Kurnia Putri; Netrawati Netrawati (Universitas Negeri Padang, 2019)
The relationship of peer social interaction in school occurs when teaching and learning activities in the classroom and outside the classroom have an important role in fostering learning motivation that can increase the activity and effectiveness of student learning. This study aims to: (1) describe the social interaction of student peers, (2) describe student learning motivation, (3) test the significance of the relationship between peer social interactions with student learning motivation. This type of research is quantitative with a descriptive correlational approach. The population of this study were students of SMA Negeri 3 Padang Panjang which numbered 881 students. The sampling technique used was purposive random sampling, so that a sample of 275 students was obtained. The instruments used were peer social interaction questionnaires and learning motivation questionnaires. Data were analyzed by descriptive statistics and Pearson product moment technique using the SPSS version 20.0 program. The results of the study describe: (1) peer social interaction is in a good category with an average achievement of 57.09%, (2) learning motivation is in the high category with an average achievement of 66.18%, and (3) there is a relationship significant between peer interactions with learning motivation with the acquisition of 0.478 at a moderate level with a significance level of 0,000. The magnitude of the correlation is 0.478, meaning that if the social interaction of peers is good, then the students' motivation also tends to be high. Conversely, if peer social interactions are not good then learning motivation tends to be low.